Conversion in the Semantic Field of “Age” in English and Armenian - Adamyan, Mariam (Bulletin of Yerevan University B: Philology, 2025)
This article investigates the phenomenon of conversion within the semantic field of "age" in English and Armenian. Conversion, which involves words shifting grammatical categories without morphological changes, is prevalent in English but less common in Armenian. This study examines the adaptation of age-related terms through this process in both languages. The findings demonstrate that English frequently employs conversion, enabling age-related terms to function flexibly as both nouns and verbs. Conversely, Armenian utilizes a more systematic approach, incorporating age terms into its inflectional morphology. This comparative analysis elucidates cultural distinctions in perceptions of aging and the life cycle, as well as the linguistic adaptability and expressiveness characteristic of each language. By focusing on age-related vocabulary, this research offers insights into broader linguistic trends and cultural perspectives. It also addresses the methodological challenges associated with identifying conversion across diverse linguistic contexts. Ultimately, this study enhances our understanding of how languages evolve to articulate universal human experiences.